Buccal habits: frequency and clinic appearance in children between 5 and 11 years - Maureen Janette Más García; Clotilde de la Caridad Mora Pérez; Raúl López Fernández (Medisur)
Background: The first step to treat incorrect habits is to detect the cause. Many of them derive from usual situations that, once detected and correctly managed, can contribute to the spontaneous suppression of the incorrect habit. Objective: To characterize a group of children between 5 and 11 years with buccal deforming habits. Methods: Observational, descriptive, correlational study including 176 children from three clinics of the quarter “Junco Sur” in Cienfuegos developed from June 2005 to June 2006. The clinical examination was performed in children, and their parents or tutors were interviewed. The frequency of buccal deforming habits was determined, as well as the presence of dental maxillofacial defects. Results: Deforming habits were identified in 60, 2% of the children; the most frequent were baby bottle suction (48%), finger suction (24%) at six years old and lingual protraction at eight years (36,1%) in girls. The dental maxillary-facial defects occurred in the 42,6% and there was a prevalence of vestibule-version at eight years (44,4%), augmented ridge at 10 years (35,4%) and bilabial incompetence at 11 years (13,3%), all of them in girls. There was prevalence in Angle´s Class I with 60, 1%. Conclusion: Buccal deforming habits are a health problem in the studied universe.